Experimental investigation of particle characteristics on pulmonary drug delivery (SEP) - Lau, Raymond Wai Man (2012)
In this study, the effect of shape and morphology of dry particles for inhalation is investigated. The optimum design of micro-particle for better delivery performance is determined. Preliminarily, different shape macro-particles with low sphericity are experimented in a confined medium to determine the impact of shape irregularities on wall effect during gravitational settling. Then different shape micro-particles including spherical, pollen, plate, cube, and needle shape particles are synthesized with a similar aerodynamic size range of <5μm. Flowability and in vitro dispersion and deposition experimentation using cascade impactor are performed with the different shape particles. Particles with shape that have preferable behavior are formulated as carrier particles for dry formulation. The flow behavior and turbulence occurrence of the particle laden gas flow are measured in an idealized inhalation path model. The feasibility of these carrier particles as a binary mixture with a model drug is also assessed. The effect of drug loading and inhalation flow rate of these carriers are assayed and compared with conventional carrier particles. Particle shape is found to influence the particle settling behavior and velocity by changing their settling orientation. Elongated particles can avoid adverse wall effect by shifting their settling orientation in the settling medium. Micro-particle flow, dispersion and deposition characteristics are not direct function of particle aerodynamic diameter (da) and characteristic size. Particle shape factor is also not able to account the inconsistencies of the irregular shape 3 particles. Pollen-shape particles with fibrous surface morphology exhibit better flow properties, in vitro emission and deposition values than other shape particles. Among the particles with a da range of 1.4-5.9 μm, pollen-shape particles result in ED values over 80% while other shape particles exhibit 50-75% at 30 L/min. The FPF value of the pollen-shape is over 15% while for other shape particles it varies in the range 2-10%. It is anticipated that surface morphology impose low surface density to the particles. They experience lower interparticle interaction and aggregation tendency which improve their flow, dispersion and deposition performance. Large pollen-shape particles show preferable flow behavior in the idealized inhalation path model. They can follow the geometry conveniently and reduce early deposition unlike the traditional lactose carriers. The binary mixture of these pollen-shape carrier particles with a model drug also proved their potential in comparison with the lactose carriers.